Gastroenteropancreatic neuroendocrine neoplasms in children and adults: a comparative review - Kuhlen, Michaela; Claus, Rainer; Pavel, Marianne E.; Kunstreich, Marina; Begum, Nehara; Lapa, Constantin; Redlich, Antje (Frontiers in Endocrinology, 2026)
BackgroundGastroenteropancreatic neuroendocrine neoplasms (GEPNENs) represent a biologically heterogeneous tumor group that is increasingly recognized in adults but remains exceptionally rare in children. While adult management is guided by evidence-based recommendations, pediatric practice relies mainly on registry data and extrapolation. A direct comparison is needed to identify shared principles, highlight divergences, and define research priorities.MethodsWe performed a structured literature review of pediatric GEPNENs (pancreatic, gastrointestinal [excluding appendix], and neuroendocrine neoplasms of unknown primary) and contrasted these findings with adult guidelines (ENETS 2023–2024, ESMO 2020–2024, ASCO 2023, NANETS 2018-2023) and pivotal clinical trials. Domains analyzed included epidemiology, clinical presentation, histological and molecular characteristics, treatment strategies, outcomes, and guideline frameworks.ResultsPediatric GEPNENs are strongly enriched for hereditary cancer predisposition syndromes (MEN1, VHL, NF1, TSC) and show a predominance of well-differentiated NET G1–G2. In contrast, adults exhibit the full spectrum of NET G1–3 and NEC G3. Somatostatin receptor (SSTR) expression is frequent in both pediatric and adult NETs, supporting the use of somatostatin analogues (SSAs) and peptide receptor radionuclide therapy (PRRT) in advanced disease; SSTR expression declines with increasing grade. Surgical resection remains the only curative option in both populations, with pediatric practice prioritizing organ preservation and minimization of late effects. In adults, systemic therapy sequencing is structured by randomized trials, whereas pediatric use of systemic therapies is adapted case-by-case, with emerging but still limited evidence. Survival in localized pediatric NETs exceeds 90%, but remains poor in metastatic and high-grade disease, similar to adults.ConclusionsAlthough histological frameworks are shared, pediatric GEPNENs differ from adult disease in genetics, site distribution, functional status, and survivorship challenges. Adult evidence may be cautiously adapted to pediatrics, but pediatric-specific guidelines and collaborative research are urgently needed to address unique biological and clinical features and to harmonize long-term care.